The Composition of Nekton as Bioindicators in Way Tahmi River at Blambangan Umpu - Pawhestri, Suci Wulan; Ardianti, Indah Marlina; Fauziah, Hanifah Nur; Andandaningrum, Della (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2025)
Way Tahmi River is a crucial freshwater source for the local ecosystem and surrounding communities, providing essential ecosystem services such as habitats for diverse species, clean water, and support for agricultural and fisheries activities. However, anthropogenic pressures, including water pollution from domestic and industrial waste, land use changes, and overexploitation of natural resources, pose significant threats to the river's ecosystem. This study aims to assess the nekton diversity in Way Tahmi River as bioindicators of water quality. The research involved sampling nekton at three different stations, each chosen based on proximity to residential areas, dining establishments, and plantations. Physical and chemical parameters, including temperature, Ph dissolved oxygen (DO), salinity, and water clarity, were measured to evaluate environmental conditions. The results indicated that the identified nekton belonged to Actinopterygii and Malacostraca classes, with varying species composition across the stations. The Shannon-Wiener diversity index showed moderate nekton diversity, while evenness and dominance indices suggested a relatively balanced and stable ecosystem. These findings highlight the importance of nekton as bioindicators and the need for effective management strategies to preserve the aquatic ecosystem of Way Tahmi River.